Probable or Inevitable? The Readiness of Teachers to Implement Inclusive Education Effectively: A case study in a Private School in Sharjah - ADNAN, HADEEL (2022)
This main objective of this research is to investigate the readiness of teachers to implement inclusive education effectively. A sample of 58 teachers of different subjects was investigated in a private school in Sharjah depending on the descriptive analytical approach. The teachers were asked to answer a questionnaire to investigate their psychological, social, cognitive and academic readiness to implement inclusive education effectively. Findings indicated that the readiness of teachers to apply inclusive education effectively was high in the four factors of the questionnaire (Psychological - Social - Cognitive - Academic). Moreover, the study showed that the teachers face many problems and challenges when teaching students with special educational needs and disabilities (SEND) in their classes, and therefore the study recommended the necessity of identifying those challenges that face the teachers, then confronting them and proposing solutions to overcome those challenges and problems.